The philosophy of education : an introduction - Schofield, Harry (Routledge library editions. Education, 2012)
There are many students who find philosophy of education difficult, because they have never received teaching in the basic essentials of general philosophy. This book begins by asking the basic question 'what is philosophy?' and examines a number of possible answers. Step by step the reader is introduced to the modern techniques of linguistic and concept analysis. Whenever a technical term is used it is explained and illustrated by reference to familiar situations in everyday life.